2015
DOI: 10.1139/cjc-2014-0561
|View full text |Cite
|
Sign up to set email alerts
|

Lactide polymerization with iron alkoxide complexes

Abstract: RésuméLes essais préliminaires pour préparer des alcoolates de fer à partir du bichlorure ou bibromure de fer (II), en les combinant avec des ligands de type diimino pyridine, ont engendré la formation de complexes homoleptiques et hétéroleptiques, dépendant des substituants sur les branches imines du ligand. Ces complexes homoleptiques octaédriques et paramagnétiques ont été étudiés par rapport à leurs propriétés spectroscopiques et cristallographiques. De plus, la synthèse des complexes de fer hétéroleptique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The regular 72 m/z difference between ions showed that transesterification took place affecting the ester bond in a pure lactid diad. While transesterification in (co)polyesters based on dilactids has been observed for various catalysts, such as Sn(oct) 2 (Kowalski et al, 2005), DBU (Meyer et al, 2010) and a Fe(II)-based ROP catalyst (Keuchguerian et al, 2015), the extent is largely differing depending on the reaction conditions, especially the temperature and some transesterification catalysts do not promote the transesterification of the ester bond of the lactide unit (Lendlein et al, 2000). In most of the conducted syntheses, the area of the peaks representing species containing an even number of lactide units was roughly equal to peaks representing species with an odd number of lactide units.…”
Section: Resultsmentioning
confidence: 99%
“…The regular 72 m/z difference between ions showed that transesterification took place affecting the ester bond in a pure lactid diad. While transesterification in (co)polyesters based on dilactids has been observed for various catalysts, such as Sn(oct) 2 (Kowalski et al, 2005), DBU (Meyer et al, 2010) and a Fe(II)-based ROP catalyst (Keuchguerian et al, 2015), the extent is largely differing depending on the reaction conditions, especially the temperature and some transesterification catalysts do not promote the transesterification of the ester bond of the lactide unit (Lendlein et al, 2000). In most of the conducted syntheses, the area of the peaks representing species containing an even number of lactide units was roughly equal to peaks representing species with an odd number of lactide units.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the investigated catalyst systems are based on metals with an empty d-shell (group 1-4 and rare earth metals) 3,7,[13][14][15][16][17][18][19][20][21][22][23] or a filled d-shell (Zn, group 13-14). [4][5][6]11,14,15,24,25 Of catalysts based on mid-range transition metals, only iron [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and copper [43][44][45][46][47][48][49][50][51][52][53][54] have been studied in somewhat more detail. Copper catalysts originally showed low to moderate activ...…”
Section: Introductionmentioning
confidence: 99%
“…Mid- to late d n -transition metal complexes, on the other hand, have been sparingly studied. Very few studies investigated the performance of Cr, Mn, or Co systems. ,, Next to iron, , copper complexes received the highest attention. We have reported that copper diiminopyrrolide complex 1 polymerizes rac -lactide with an isoselectivity of P m = 0.7 at room temperature (Scheme ). Isoselective stereocontrol was unprecedented for copper complexes.…”
Section: Introductionmentioning
confidence: 99%